Formulation and Evaluation of Wound Healer Waterproof Spray containing Cymbopogon nardus L. and Musa paradisiaca L. Leaves Wax - Novitasari, Putri Rachma; Dwi Nugroho, Agung; Adyaqsa Prihatmadi, Farhan; Kesya Riza Purnama, Sarasevita (Journal of Food and Pharmaceutical Sciences, 2024)
Red lemongrass (Cymbopogon nardus L.) is an Indonesian plant which has potential as a wound healer. Red lemongrass contain essential oil which has the potential effect to treat wounds, such as citral. The citral content in every 1 mL of this essential oil is 32.28%. A wound is an injury-induced disturbance of the tissues' normal anatomical relationships. Wound is basically prone to infection, and it can infect bacteria, such as Staphylococcus aureus bacteria. Water splashes exposed the Staphylococcus aureus bacteria, which then caused an infection. Water is a medium for bacterial growth. In this research, kepok banana leaves wax (Musa paradisiaca L.) is added as a waterproof base to prevent wounds from being splashed by water, because wounds on skin tissue are protected by a layer of wax originating from kepok banana leaves (Musa paradisiaca L.). The aim of this research was to make a waterproof gel spray from red lemongrass essential oil using wax of banana leaves as a waterproof base. The result showed waterproof gel spray preparation has yellowish white colour; a distinctive aromatic odor, pH 6,28; viscosity 135 cps, and dry time 7.5 minutes and it has waterproof properties.